Valorization of expired dairy products by anaerobic digestion - Marin, Danieli Fernanda Canaver [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
The dairy industry is an important sector of the food industry, producing 928 million tons of milk in 2021. However, this sector is responsible for generating a high amount of waste, such as expired dairy products (EDP). Currently, the main destination of EDP are their disposal in landfills, causing environmental problems due to their high organic matter content. In this sense, this study proposed to evaluate strategies for using and valorizing EDP, transforming them into resources for bioproducts generation from anaerobic digestion (AD). As the first strategy, an autochthonous mixed culture was obtained from EDP using anaerobic batch reactors with All Purpose Tween (APT) culture medium as substrate. The Lactobacillus genus was identified with the highest relative abundance in the obtained culture with 78.4%. Subsequently, the autochthonous mixed culture was evaluated in anaerobic reactors using different substrates (xylose, arabinose, fructose, maltose, glucose, rhamnose, lactose, sucrose, EDP, and banana processing wastewater (BPW)). The mixed autochthonous culture grew on all tested substrates, with high carbohydrate removal (57.6-97.0%), producing lactic acid (LA) as the predominant soluble metabolite (2.40-7.85 g L-1). The highest LA yield was obtained from BPW with 0.98 g g-1. As the second strategy, it was evaluated the co-digestion of EDP with synthetic sewage (SS) in single-stage anaerobic reactors. Five assays were performed with the following percentages of EDP in the substrate mixture (1) 0%, (2) 5.0%, (3) 7.5%, (4) 10.0%, and (5) 15, 0% (v/v). Higher COD removal (89.2%) and higher CH4 production (6583.6 NmL L-1) were verified in Assay 4 (10.0% EDP). Higher CH4 yield were obtained in Assay 3 (7.5% EDP) with 332.6 NmL gVSadd-1. Acetoclastic (Methanosaeta) and hydrogenotrophic (Methanolinea, Methanoregula, and Methanobacterium) archaea were identified in assays 2, 3, and 4 (5.0% to 10.0% EDP), which probably contributed to the high efficiency of organic matter removal and high methane production. Assay 5 (15.0% EDP) was inhibited due to the accumulation of volatile acids in the anaerobic reactors. As the last strategy, the co-digestion of EDP with SS was evaluated from two-stage anaerobic systems. In the first stage (acidogenic reactors), three assays were assembled with the following substrate composition (v/v): (1) 10% EDP + 90% SS, (2) 15% EDP + 85% SS, and (3) 20% EDP + 80% SS. The liquid effluents generated at the end of the acidogenic stage of assays 1, 2, and 3 were used as substrates in the second stage (methanogenic reactors), corresponding to tests 4, 5, and 6, respectively. In the first stage, higher carbohydrate removal (92.3%) and higher hydrogen production (1309.3 NmL Lr-1) were obtained in Assay 3 (20% EDP + 80% SS). In the second stage, higher COD removal (94.7%) and methane production (6813.4 NmL Lr-1) were verified in Assay 5 (15% EDP + 85% acidified SS). Assay 6 (20% EDP + 80% acidified SS) was inhibited due to the accumulation of volatile fatty acids (11427.9 mg L-1), mainly acetic acid (8455.6 mg L-1). Thus, the experimental approaches of the studies carried out offer promising opportunities for EDP valorization through its application in biological processes. In addition, the use of expired dairy waste can contribute to its recovery by providing bioproducts and biofuels obtained from renewable sources.

A indústria de laticínios é um importante setor da indústria de alimentos com produção de 928 milhões de toneladas de leite em 2021. Entretanto, esse setor é responsável pela geração de uma elevada quantidade de resíduos, como os produtos lácteos vencidos (PLV). Atualmente, a principal destinação dos PLV é a sua disposição em aterros sanitários, causando problemas ambientais devido à sua elevada carga orgânica. Neste sentido, esse estudo propôs avaliar estratégias de utilização e valorização de PLV transformando-os em recursos para a geração de bioprodutos a partir do processo de digestão anaeróbia (DA). Como primeira estratégia uma cultura autóctone mista foi obtida a partir dos PLV usando reatores anaeróbios em batelada alimentados com meio de cultura All Purpose Tween (APT) como substrato. O gênero Lactobacillus foi identificado com maior abundância relativa na cultura obtida com 78.4%. Posteriormente, a cultura mista autóctone foi avaliada em reatores anaeróbios utilizando diferentes substratos (xilose, arabinose, frutose, maltose, glicose, ramnose, lactose, sacarose, PLV, e água residuária do processamento da banana (ARPB)). A cultura autóctone mista cresceu em todos os substratos testados, com elevadas remoções de carboidratos (57.6-97.0%) e produção predominante de ácido lático (AL) como metabólito solúvel (2,40-7,85 g L-1). O maior rendimento de produção de AL foi obtido a partir da ARPB com 0,98 g g-1. Como segunda estratégia, foi avaliada a co-digestão dos PLV com esgoto sintético (ES) em reatores anaeróbios em único estágio. Cinco ensaios foram realizados com as seguintes porcentagens de PLV na mistura de substratos (1) 0%, (2) 5,0%, (3) 7,5%, (4) 10,0%, e (5) 15,0% (v/v). A remoção mais elevada de DQO (89,2%) e maior produção de CH4 (6583,6 NmL L-1) foram verificadas no ensaio 4 (10,0% PLV). O rendimento mais elevado de CH4 foi obtido no ensaio 3 (7,5% PLV) com 332.6 NmL gVSadd-1. Archaeas acetoclásticas (Methanosaeta) e hidrogenotróficas (Methanolinea, Methanoregula e Methanobacterium) foram identificadas nos ensaios 2, 3 e 4 (5,0% a 10,0% PLV), o que provavelmente contribuiu para a eficiência elevada de remoção de matéria orgânica e alta produção de metano. O Ensaio 5 (15.0% PLV) foi inibido devido ao acúmulo de ácidos voláteis nos reatores anaeróbios. Como última estratégia, a co-digestão de PLV com ES foi avaliada a partir de sistemas anaeróbios em dois estágios. No primeiro estágio (reatores acidogênicos), foram montados três ensaios com a seguinte composição de substrato (v/v): (1) 10% PLV + 90% ES, (2) 15% PLV + 85% ES, e (3) 20% PLV + 80% ES. Os efluentes líquidos gerados ao final da etapa acidogênica dos ensaios 1, 2 e 3 foram utilizados como substratos no segundo estágio (reatores metanogênicos), correspondendo aos ensaios 4, 5 e 6, respectivamente. No primeiro estágio, a remoção mais elevada de carboidrato (92,3%) e maior produção de hidrogênio (1309.3 NmL Lr-1) foram obtidas no ensaio 3 (20% PLV + 80% ES). No segundo estágio, a remoção mais elevada de DQO (94.7%) e produção de metano (6813.4 NmL Lr-1) foram verificadas no ensaio 5 (15% PLV + 85% ES acidificado). O ensaio 6 (20% PLV + 80% ES acidificado) foi inibido devido ao acúmulo de ácidos graxos voláteis (11427,9 mg L-1), principalmente ácido acético (8455,6 mg L-1). Assim, as abordagens experimentais dos estudos realizados oferecem oportunidades promissoras para a valorização do PLV através da sua aplicação em processos biológicos. Além disso, a utilização de resíduos lácteos vencidos pode contribuir na sua valorização com o fornecimento de bioprodutos e biocombustíveis obtidos a partir de fontes renováveis.
Valorização de produtos lácteos vencidos por digestão anaeróbia
Keywords: Biotechnology; Bioreactors; Methane; Hydrogen; Lactic acid; Biotecnologia; Biorreatores; Metano; Hidrogênio; Acido láctico